Human Parainfluenza Serotype 3 Viral Myocarditis Complicated with Ventricular Tachycardia (Archives of Clinical and Medical Case Reports, 2021)
Background: Viral myocarditis is a leading cause of mortality and cardiovascular morbidity. Its clinical manifestation is heterogeneous varying from asymptomatic courses to presentations with ventricular arrhythmias, heart failure and cardiogenic shock. Right ventricular endomyocardial biopsy is the gold standard in confirming the diagnosis; however, this may not be readily available in some clinical settings. For identification of the viral causative agent, the expanded use of polymerase chain reaction (PCR) techniques may facilitate precise viral genomic diagnosis and improve outcomes. Case presentation: We report a case of a 56 -year-old female patient who presented to the hospital with chest pain mimicking an acute coronary syndrome and stable monomorphic ventricular tachycardia. She had a medical history notable for permanent pacemaker placement due to high-degree atrioventricular block, Brugada-like syndrome and venous thromboembolic disease. Her high-sensitivity troponin was elevated, evidence of myocardial injury, and an echocardiogram showed an ejection fraction of 55% with no wall motion abnormalities. She was managed with IV Amiodarone with subsequent cardioversion. Coronary angiography performed after cardioversion ruled out ischemia as the cause of her ventricular tachycardia. Examination of the nasopharyngal swap by PCR showed a Human Parainfluenza Virus type 3 (HPIV-3), the most likely culprit for her myocardial injury. The presumptive diagnosis of myocarditis complicated with ventricular tachycardia was made after ruling out other common etiologies. Conclusion: This case illustrates a mild presentation of myocarditis and the diagnostic challenge that may ensue due to the lack of specificity of their clinical presentation and the limitation to perform biopsies or cardiac magnetic resonance imaging.